Beauty class training for ethics and skills level for STEBIS IGM Sharia economics students - Yanti Maleha, Nova; Aliah Ghina (Jurnal Ekonomi, 2024)
This service discusses beauty class training at the ethics and skills level of sharia economics students at STEBIS Indo Global Mandiri Palembang. This happens because of the importance of ethics and one's appearance when entering the world of work and society where currently there are still female students who do not pay attention to ethics in appearance. The aim of the training offered is to improve cosmetology skills and increase their self-confidence, beauty class levels of ethics and skills for students are part of self-development. This training is carried out by presenting tutors and models to act as examples for the training participants. The results of this training show that students are able to look good and have an ethical appearance not only in terms of physical appearance but also attitude. This is very useful for students as preparation when entering the world of work and for those who have an interest in the beauty business when they graduate